The X-files Book of the Unexplained - Goldman, Jane, 1970- (London Simon & Schuster, 1996)
An exploration of unexplained phenomena which have been used as the basis for episodes of the television series, "The X-Files". The mysteries incorporate UFOs, abduction, vampires, voodoo, spontaneous human combustion, genetic mysteries, ghosts, reincarnation and freaks of nature
Include Color Illustration and Bibliography
Keywords: Curiosities and wonders -- Parapsychology -- X-files (Television program)